Flow assurance study based on hydrate deposition modeling - Li, Junliang; Cai, Meng; Wei, Na (Frontiers in Energy Research, 2025)
During throttling and pressure reduction, hydrates can form due to changes in pipeline pressure, particularly in natural gas with high water content. The formation of hydrates obstructs gas flow, even in minimal quantities, resulting in elevated differential pressure and accelerating hydrate formation, which leads to technical challenges such as diminished production and pressure retention. This study introduces and verifies a multi-field coupling risk prediction model for hydrate blockages in natural gas pipelines. The model integrates the temperature field, pressure field, multiphase flow theory, and hydrate clogging theory. Based on this foundation, the impacts of inlet temperature, pressure, and gas volume on the formation of hydrates in pipelines were analyzed, and the most vulnerable blocked point and the maximum formation rate were determined for different sensitivity factors. The results show that elevated inlet pressure and reduced inlet temperature enhance the maximal hydrate formation rate, while gas volume exerts a negligible influence. And increasing gas transport will move the most susceptible blockage point downstream. Finally, the original model is used to forecast actual gas hydrate plugging using time discretization and iterative calculation approaches.